Taburan ostrakod di dalam sedimen luar pantai di sekitar Pulau Tinggi, Johor = Distribution of ostracods in offshore sediment around Pulau Tinggi, Johor - Noraswana Nor Faiz; Ramlan Omar; Basir Jasin (Universiti Kebangsaan Malaysia, 2007)
A study was conducted to determine the distribution of ostracods in offshore sediment around Pulau Tinggi, Johor. A total of 11 stations were determined as sampling area. The abundance of ostracods is high in this study area. A total of 1,975 specimens were found belonging to 16 families, 36 genera and 51 species. Family Trachyleberididae has the highest diversity of species with 19 species recorded and the most dominant family with 589 specimens. The most dominant species is Loxoconcha malayensis with 131 specimens. Several in-situ physico-chemical parameters such as temperature, dissolved oxygen (DO), depth, salinity and pH were measured. The range values for each of these parameters are 26.29-29.02oC, 4.49-6.87 mg/l, 8.30-35.00 m, 34.01-38.90 ppt and 8.11-8.20, respectively. For ex-situ physico-chemical parameters such as percentage of organic matter, sand, clay and silt, the range values for each parameters were 4.91-10.73%, 88.41-97.26%, 0.84-7.49% and 1.89-6.22%, respectively. The sediment texture in this study area can be categorized as fine, medium and coarse sand. The most dominant texture is medium sand. Correlation analysis shows that salinity, the percentages of organic matter, clay and silt are positively and significantly correlated with the abundance of ostracods while temperature and percentage of sand are negatively and significantly correlated with ostracod abundance. Other parameters do not show any significant correlation.